Scaling up to speed up? A critical evaluation of programme management in Indonesian megaproject development. (11th October 2019) - ; Prakoso, Yudhi Timor Bimo; Witte, Patrick; Spit, Tejo
For decades, policymakers in developing countries have used megainfrastructure project development to achieve economic growth. However, in practice, megaproject management does not live up to this ambition due to the contradiction between the temporary organisation of megaproject management and the long-term strategic goals embedded. Because of this, there is a strand of literature advocating programme management approach to counteract the complexity of megaproject development. This paper aims to contribute to the literature both on megaproject and programme management by providing a critical evaluation of programme management in dealing with these contradictions, particularly in the case of developing countries. The paper reflects on a case study of the acceleration programme of infrastructure projects in Indonesia through a content analysis and in-depth interviews with key stakeholders and experts. The findings show ineffective and inefficient interaction at the project level, especially in dealing with dynamic power relations and unfamiliar funding schemes.